Efektifitas Herbisida Formulasi pada Gulma Air di Lahan Rawa Tadah Hujan, Rawa Payau dan Saluran Drainase - Anwar, Risvan; Suzanna, Eka; Djatmiko, Djatmiko; Dwi Andika, Windi Sambaz; Gartiwo, dan M. Tanu (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
A series of studies had been carried out to create new types of herbicides. The studies had found six formulations ofherbicides. This study aimed to determine the effectiveness of herbicides formulation in controlling aquatic weeds. Theexperiment used a randomized complete block design with seven herbicide formulations as treatments and three replications.The seven formulations of herbicide were: Unihaz 1, Unihaz 2, Unihaz 3, Unihaz 4, Unihaz 5, Unihaz 6, and a control(glyphosate 2 kg ha-1). The results of the study found that there were 21 species of weed in rainfed swamps, ten species inbrackish swamps and one species namely water hyacinth (Eichhornia crassipes) in drainage channel. Herbicide formulationsof Unihaz 3, 4, 5, and 6 were effective in controlling aquatic weeds in rainfed swamps. Herbicide formulations of Unihaz 2, 3and 5 were effective in controlling aquatic weeds in brackish swamps. All herbicides formulations were effective in controllingweeds in drainage channels. Moreover, herbicide formulation of Unihaz 5 was more effective in controlling aquatic weeds inrainfed swamps, brackish swamps and drainage channels than other formulations, and it was not significantly different fromthe use of a glyphosate dose of 2 kg ha-1.Keywords: Eichhornia crassipes, fermented coconut water, organic herbicide, new types of herbicides